Production of Extracellular Proteins by the Biocontrol Fungus Gliocladium virens - van Tilburg, A.-U. B. (1993)
Gliocladium virens is a common saprophytic fungus that is mycoparasitic on a large number of fungi. Responses of G. virens toward its environment were examined by monitoring the presence of extracellular proteins in culture fluid during time course experiments. Culture fluid of G. virens grown on glucose, washed cell walls of Rhizoctonia solani (one of its hosts), olive oil, or chitin contained β-glucanase, N-acetylglucosaminidase, lipase, and proteinase activities. There were relatively minor amounts of other enzymatic activities tested. Levels of extracellular enzyme activity varied with the age of the culture and the substrate used as the carbon source. Substrate-associated differences in enzyme activities were detected as early as 8 h after transfer of mycelia from stationary-phase cultures to fresh media. When G. virens was grown on host cell wall material, β-glucanase had the greatest specific activity of any enzyme tested at 8 h. This result suggests that β-glucanase may be the first enzyme important in the G. virens-R. solani interaction. Analysis by sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed that some of the polypeptides were present in the culture fluid at relatively constant amounts and others accumulated early, at intermediate times, or late in the 8-day incubation test period. Several of the polypeptides present in the culture fluid during the first 24 h disappeared completely by 48 h. Consequently, it appears that extracellular proteins in cultures of G. virens are regulated by a combination of gene regulation and protein degradation.